Advancing Collaborative Competence: Instrumentation Development and Integration Strategies for Effective Learning - Peni Suharti; Lina Listiana; Ruspeni Daesusi; Sri Sutarni; Rita Rahmaniati; Yusuf Zakaria; Emese Kovácsné Nagy (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Collaboration skills are one of the 21st-century skills that are important to develop for stu-dents because they are life tools needed when continuing their studies in school, engaging in society, and in the world of work. As a result, teachers must facilitate students' collaboration skills and measure them. Valid, reliable, and effective instruments are needed to measure students' collaboration skills. This study aims to develop an instrument to measure students' collaboration skills. This research uses a 4-D development model of defining, designing, developing, and Disseminating. At the define stage, it was found that many teachers still needed instruments to measure collaboration skills and determine indicators of collaboration skills. The design results obtained are collaboration instruments in learning. These consist of 9 indicators: contribution, time management, problem-solving, working with others, investi-gative techniques, quality of work, focus on tasks, readiness, and monitoring group effecti-veness. Next, scoring is determined. The instrument was validated by experts and tested in 2 trials. The first trial was conducted at SMAM 7 and SMAM 3 Surabaya in class XI. Vali-dity results stated that the instrument was very valid. The results of trials using the IBSC learning model show that the instrument is reliable and considerably effective in measuring collaboration skills. The novelty of this study resulted in a collaborative instrument worthy of use both theoretically and empirically.